PENGARUH MODAL DAN SKILL TERHADAP MINAT MAHASISWA MENJADI ENTREPRENEUR (STUDI PADA MAHASISWA JURUSAN EKONOMI SYARIAH IAIN PADANGSIDIMPUAN) - Darwis Harahap (Institut Agama Islam Negeri Padangsidimpuan, 2017)
The background of this study is a phenomenon that occurs in students of the Islamic Economics Department of the Padangsidimpuan State Islamic Institute who have an interest in becoming an entrepreneur / entrepreneur. The formulation of the problem in this study is whether there is an influence of capital and skills on students' interest in becoming entrepreneurs. This study aims to determine the effect of capital and skills on students' interest in becoming entrepreneurs. The usefulness of this research is to increase knowledge in the field of entrepreneurship, as an input to becoming more advanced and motivated entrepreneurs to increase students' interest in becoming entrepreneurs. This study discusses the theories relating to entrepreneurship science, namely the theoretical approach regarding students' interest in becoming entrepreneurs who are influenced by capital and skill factors. This research was conducted in February 2017 in the Department of Islamic Economics, Faculty of Economics and Business, Islamic State Institute of Padangsidimpuan. This type of research is quantitative research. The population in this study were students of the Islamic Economics Department from 2013 to 2015. The samples in this study were 88 respondents. Data sources were obtained from primary data with data collection techniques, namely distributing questionnaires to students of the Department of Islamic Economics from 2013 to 2015 at random. Test instruments using validity and reliability tests. The analytical method used is multiple linear regression analysis, descriptive analysis, normality test, linearity test, multicollinearity test and heterocedasticity test. Testing the hypothesis used is a statistical test simultaneously (F test) and a statistical test partially (t test) with a significant level of α = 10%. The test results with multiple linear regression analysis obtained ME equation = 9,249 + 0,253M + 0,444S. Simultaneous test results obtained Fcount = 29,887 Ftable = 2,366 with a significant level of 0,000 0,1 this can be concluded that capital and skills have a significant effect on students' interest in becoming entrepreneurs. Partial test results obtained tcount Ttable = 3.483 1.663 which indicates that there is an influence of capital towards students 'interest in becoming entrepreneurs and there is influence of skills on students' interest in becoming entrepreneurs with partial test results obtained tcount ttable = 4.541 1.663. Keywords: Capital, Skill, Interest in becoming an Entrepreneur